Analisis Hukum Kepesertaan Pekerja Mandiri Dalam Pelaksanaan Program Penyelenggaraan Tabungan Perumahan Rakyat - Nabila Haviazzahra; Muhamad Hasan Sebyar (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The provisions requiring an Independent Worker to become a participant in the implementation of Public Housing Savings (Tapera) are felt to be inadequate/or unfair. If this continues to be forced, then at least 2 (two) problems will arise in the future, namely: First, how will the participation of Independent Workers continue. Second, whether the provisions requiring the participation of Independent Workers are in accordance with the principle of utility (utilitarianism) in law. The aim of the research is to contribute ideas to regulatory or policy makers regarding the implementation of Tapera. The research method chosen is normative legal research, which is related to doctrinal research or legal teachings by conducting literature reviews, through a legal philosophy approach with the thought framework of Jeremy Bentham (utilitarianism) and a legislative approach. The results of the assessment (thinking) are as follows: First, the continuity of Independent Worker participation will have a high risk of being resolved until the end. Second, Jeremy Bentham's principle of utilitarianism/benefit (happiness) justice is not implemented, considering the norm which requires Independent Workers to follow Tapera, it is felt that it is unfair in the event that Independent Workers already own a house (either by paying in installments, building their own house, getting a house from from gifts and inheritance).